Rocuronium Versus Suxamethonium for Rapid Sequence Induction of General Anesthesia for Cesarean Section: Influence on Neonatal Outcomes. Issue 3 (September 2018) - Kosinova, M.; Stourac, P.; Adamus, M.; Seidlova, D.; Pavlik, T.; Janku, P.; Krikava, I.; Mrozek, Z.; Prochazka, M.; Klucka, J.; Stoudek, R.; Bartikova, I.; et al.
Abstract : ( Int J Obstet Anesth 2017;32:4–10) Rocuronium has been considered for use in rapid-sequence induction of general anesthesia for cesarean delivery as an alternative to succinylcholine. No large, randomized trials have investigated neonatal outcomes associated with maternal administration of rocuronium. A previous trial by the same authors as the present study compared rocuronium and succinylcholine for cesarean delivery and found lower Apgar scores at 1 and 5 minutes for neonates whose mothers were administered rocuronium. However, this was a secondary outcome of the earlier study and was not adequately powered for that outcome. Therefore, the investigators performed this current study with the goal to confirm these findings in a larger sample size.